2021
DOI: 10.1371/journal.pone.0258765
|View full text |Cite
|
Sign up to set email alerts
|

What drives small-scale farmers to vaccinate their multiple livestock species animals against common infectious diseases in Myanmar?

Abstract: Livestock rearing is an important income source for small-scale farmers in Myanmar, but Foot and Mouth Disease (FMD) and Newcastle disease (ND) are major constraints to livestock production. A study was conducted to identify perceptions of farmers about FMD and ND disease risks and perceptions about vaccination practices by using the modified health belief model. The majority of livestock farmers (>70%) reported that they were aware of the risk and impact of FMD and ND and were willing to vaccinate their li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The livestock farmers periodically vaccinate, monitor disease signs and symptoms, treatment and promotion of hygiene in homes. This could perhaps be due to the triggers such as ownership and livestock being taken as a source of livelihood for some communities [25]. Therefore, a farmer would do all it takes to ensure that the animals are safe from diseases such as cryptosporidiosis which would rather claim lives of their animals.…”
Section: Discussionmentioning
confidence: 99%
“…The livestock farmers periodically vaccinate, monitor disease signs and symptoms, treatment and promotion of hygiene in homes. This could perhaps be due to the triggers such as ownership and livestock being taken as a source of livelihood for some communities [25]. Therefore, a farmer would do all it takes to ensure that the animals are safe from diseases such as cryptosporidiosis which would rather claim lives of their animals.…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated that despite not achieving the desired vaccination coverage, the large-scale FMD immunization program was highly received by participating farmers and was successful in halting the spread of the disease in Laos. According to [16], The main obstacle to vaccination was a lack of vaccine coverage in villages, whereas more than double the number of small ruminant farmers compared to cattle farmers and village chicken farmers said they did not know about immunizations and did not have the resources to perform them. In smaller villages, vaccine availability and vaccine providers were more limited.…”
Section: Awareness Of Cattle Farmers Toward Fmd Outbreaks and Vaccina...mentioning
confidence: 99%
“…Such interventions have the major advantage or creating accessibility of information. Taking the example of vaccination, a farmer's beliefs in the effectiveness of vaccinations plays a major role in their willingness to carry it out on their own livestock (Win et al, 2021).…”
Section: Awareness and Knowledge Interventionsmentioning
confidence: 99%